New vaccine strategies against enterotoxigenic Escherichia coli: II: Enhanced systemic and secreted antibody responses against the CFA/I fimbriae by priming with DNA and boosting with a live recombinant Salmonella vaccine - Lásaro,M.O. (1999)
The induction of systemic (IgG) and mucosal (IgA) antibody responses against the colonization factor I antigen (CFA/I) of enterotoxigenic Escherichia coli (ETEC) was evaluated in mice primed with an intramuscularly delivered CFA/I-encoding DNA vaccine followed by two oral immunizations with a live recombinant Salmonella typhimurium vaccine strain expressing the ETEC antigen. The booster effect induced by the oral immunization was detected two weeks and one year after the administration of the DNA vaccine. The DNA-primed/Salmonella-boosted vaccination regime showed a synergistic effect on the induced CFA/I-specific systemic and secreted antibody levels which could not be attained by either immunization strategy alone. These results suggest that the combined use of DNA vaccines and recombinant Salmonella vaccine strains can be a useful immunization strategy against enteric pathogens.